Customer experience management in B2B markets : CXM value propositions and archetypical CXM strategies - Wirtz, Jochen; Kowalkowski, Christian; Jaakkola, Elina; Holmlund, Maria; Ulaga, Wolfgang; Ahmed, Tanvir (Elsevier, 2025)
The business-to-business (B2B) customer experience (CX) literature tends to promote a one-size-fits-all approach, advocating the undifferentiated goal of exceptional CX with the view that 'more is better' in CX management (CXM). In contrast, we identify three universal customer goal categories and their associated CXM value propositions that underpin both collective and individual experiences. These categories are: (1) Relieving CX to promote organizational efficiency and individual convenience; (2) Enabling CX to facilitate organizational differentiation and individual empowerment; and (3) Enriching CX to foster organizational association and individual relationships. We also contend that firms may adopt different strategic approaches to CXM depending on their customers' goals and related value propositions. Specifically, we introduce four archetypical CXM strategies that differ in impact and scope: CXM Champion, Cherry Picker, Minimalist, and Fashionista. Finally, we propose a research agenda on CXM strategy drivers and contextual factors. For practitioners, we offer a four-step CXM strategy guide.